Nosotros que sentimos diferente - Motta, Cristina,; Motta, Carlos, (Biblioteca universitaria. Ciencias sociales y humanidades. Colección Equidad y justicia., 2012)
We Who Feel Differently is a database documentary that addresses critical issues of contemporary queer culture. It features interviews with fifty queer academicians, activists, artists, radicals, researchers, and others in Colombia, Norway, South Korea and the United States about the histories and development of Lesbian, Gay, Bisexual, Trans, Intersex, Queer and Questioning (LGBTIQQ) politics. The project discusses the notions of sexual difference, equality, citizenship and democracy in relation to sexual orientation and gender identity.